C3 chirality in polymerization catalysis: a highly active dicationic scandium(III) catalyst for the isoselective polymerization of 1-hexene - Ward, Benjamin D.; Bellemin-Laponnaz, Stéphane; Gade, Lutz H. (Angewandte Chemie. International edition, 2005)
A tactical approach: C3-chiral ancillary ligands such as tris(oxazolinyl)ethane allow stereocontrol in olefin polymerization (see scheme). An alkyl ScIII catalyst polymerizes 1-hexene with activities ranging from 2000 to 36 000 kg mol−1 h−1 (at −30 to +21 °C) and good tacticity control at low temperatures.
Gesehen am 15.12.2022